Serum Neopterin Levels and the Clinical Presentation of COVID-19 - Koc, Deniz Ogutmen; Sipahi, Hande; Surmeli, Cemile Dilsah; Calik, Mustafa; Bireroglu, Nilgun; Oksuz, Sila; Sahin, Gonul (De Gruyter Poland Sp Z O O, 2020)
In Coronavirus disease 2019 (COVID-19), it is important to evaluate disease activity and investigate possible biomarkers. Therefore, in this study, we investigated the relationship between disease activity and serum levels of possible immune activation marker neopterin in patients with COVID-19. The study enrolled 45 patients (23 females, 51.1%) treated for COVID-19. The patients were divided into two groups according to their clinical presentation: those who recovered quickly (Group 1) and those who worsened progressively (Group 2). The neopterin and C-reactive protein levels were high in all patients on admission. In Group1, neopterin concentrations and serum neopterin/creatinine ratios were significantly higher on admission compared to Day 14 of the disease, whereas in Group 2, levels were significantly higher at Day 14 of the disease than on admission. Neopterin levels at admission were significantly higher in Group 1. The serum neopterin concentrations at admission were markedly higher in patients with a derived neutrophil-lymphocyte ratio (dNLR) > 2.8 compared to those with a dNLR <= 2.8 (p < 0.05). Serum neopterin levels can be used as a prognostic biomarker in predicting disease activity in COVID-19.
Keywords: Coronaviruses; neopterin; immune activation; biomarker